2006
DOI: 10.1074/jbc.m510993200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Human Ubiquitin-specific Protease 15 DUSP Domain

Abstract: Ubiquitin-specific proteases (USPs) can remove covalently attached ubiquitin moieties from target proteins and regulate both the stability and ubiquitin-signaling state of their substrates. All USPs contain a conserved catalytic domain surrounded by one or more subdomains, some of which contribute to target recognition. One such specific subdomain, the DUSP domain (domain present in ubiquitin-specific proteases), is present in at least seven different human USPs that regulate the stability of or interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…One study demonstrated that the Asp/Asn residue is required for polarization of His residue to stabilize the catalytic activity of DUBs [14]. In USP15, delineation of amino acid sequence of the catalytic domain reveals the existence of six conserved boxes and the catalytic triad composed of Cys, His, and Asp residues, which are localized at Box 1, Box 5, and Box 6, respectively [11]. The subsequent study further revealed that the presence of two Cys-X-X-Cys motifs within Box 3 and Box 4 is critical for formation of a zinc-binding motif, which is important for conformational stability [15].…”
Section: The Structure and Function Of The Usp15 Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated that the Asp/Asn residue is required for polarization of His residue to stabilize the catalytic activity of DUBs [14]. In USP15, delineation of amino acid sequence of the catalytic domain reveals the existence of six conserved boxes and the catalytic triad composed of Cys, His, and Asp residues, which are localized at Box 1, Box 5, and Box 6, respectively [11]. The subsequent study further revealed that the presence of two Cys-X-X-Cys motifs within Box 3 and Box 4 is critical for formation of a zinc-binding motif, which is important for conformational stability [15].…”
Section: The Structure and Function Of The Usp15 Domainsmentioning
confidence: 99%
“…Ubiquitin-specific proteases (USPs), ovarian tumor proteases (OTUs), ubiquitin C-terminal hydrolases (UCHs), and Machado-Joseph disease proteases (MJDs) are categorized into papain-like cysteine proteases, while JAB1/MPN/Mov34 proteases (JAMMs) belong to zinc-dependent metalloproteases [10]. In this review, we focus on the ubiquitin carboxyl-terminal hydrolase 15 (also known as ubiquitin-specific-processing protease 15, USP15), which features two consensus sequences harboring a classical catalytic triad (Cys-His-Asp) [11]. The amplification of USP15 gene has been previously identified in glioblastoma, breast cancer and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Loop 2 (L2) comprising residues Gly 76 -Asp 111 in hUSP11 (Figure 1B) is tethered to the DUSP surface by interactions from residues Pro 85 and Ile 88 with Trp 66 from α-helix 2. These residues form part of the signature PGPI sequence identified by bioinformatic analysis as being shared by DUSP domains from seven distinct USPs, 36 but the second proline is substituted by Cys 87 in hUSP11DU. Prior to strand S2 there is a turn spanning residues Glu 108 -Asp 111 that contains several acidic residues with the sequence EGED.…”
Section: Resultsmentioning
confidence: 99%
“…The C-region harbors the enzymatic core responsible for deubiquitylation activity1213, so the C-cluster presumably recognizes the ubiquitin moiety of the ubiquitylated mysterin. Previous structural studies demonstrated that the DUSP domain of USP15 exposes multiple hydrophobic patches on its molecular surface, which are predicted to mediate protein–protein interactions via hydrophobic interactions2930. Indeed, USP15 specifically binds to SART3 (also known as Tip110) via DUSP domain and removes ubiquitin from both SART3 and its binding partner, histone H2B92728.…”
Section: Discussionmentioning
confidence: 99%